Corporate performance and managerial remuneration - Murphy, Kevin J. (Journal of Accounting and Economics, 1985)
Economic theories of efficient compensation predict a positive relationship between executive pay and corporate performance, and yet efforts to document this relationship have been largely unsuccessful. In this paper, we argue that previous cross-sectional studies have omitted important variables which seriously bias their results. Using data that focus on individual executives over time, we find that executive compensation is strongly positively related to corporate performance as measured by shareholder return and growth in firm sales. The results are robust to the stock market performance measure utilized.